Marco referencial Potencialización pymes agropecuarias y agroindustriales del Meta, a través del mercado de commodities: Referential framework Potentialization of agricultural and agroindustrial SMEs of Meta, throungh the commodities market (Revista "Boletín el Conuco", 2021)
work that contains the theoretical, conceptual,legal, institution and state of the art frameworkthat are constituted as a structure for the development of the research Project, which aims toidentify convergent actions to potentiate the agricultural and agroindustrial sector of the MetaDepartament, through the commodities market.In relation to the abovem it is relevant to deepen the existing theories, regulations, policies andprograms, since they provide guidance, conceptualizatioin, reference search, wich would leadto designing strategies to improve the access ofagricultural and agroindustrial producers to theStock Exchange Mercatile of Colombia and increase the use of its productive potential.The result of the construction of the referentialframework provides the analysis and interpretation of current theories, laws, norms and policiesas support for the socpe of the proposed objectives and the methodological development of theresearch.
Keywords: Commodity market, agricultural and agroindustrial SMEs